Towards the Technology of Oneness: The Scope of Digital Democracy and its Effectiveness in a Nation Staten - V S Devi; Chellerian, B. Sonia (International Journal of Psychosocial Rehabilitation, 2020)
Digital democracy or e-democracy refers to the application of digital media and Information and Communication Technology (ICT) in the governance of a nation state. It presumes that all the adult citizens of a country can equally participate in the development and decision making process of a nation. It enables a secure and wider participation of the public in the political environment. The paper analyzes effectiveness of the digital initiatives of the government of a nation, the challenges involved in reaching out to the public, the scope of digital governance in the future and how successful digitalization can be, in order to promote the participation of people in policy making process. An analysis of the active participation and contribution of individuals to promote the social and economic growth of the nation will also be carried out in the paper.